Synthesis of novel dual target inhibitors of PARP and HSP90 and their antitumor activities. Issue 9 (1st May 2020) - Lin, Shanshan; Zhang, LingYu; Zhang, Xiao; Yu, Zelei; Huang, Xiuwang; Xu, Jianhua; Liu, Yang; Chen, Limin; Wu, Lixian
Graphical abstract: Abstract: Poly (ADP-ribose) polymerase (PARP) inhibitors have achieved great success in clinical application, especially for the prolonged survival of cisplatin-sensitive ovarian cancer patients. However, there are still many patients who do not respond to PARP inhibitors. Novel PARP inhibitors with higher activity are urgently needed. Herein we report a series of compounds by molecular hybridization PARP-1 inhibitor Olaparib (Ola) with HSP90 inhibitor C0817 (one curcumin derivative). All synthesized compounds were evaluated for their antiproliferative activity in vitro, and some were further assessed for their inhibitory activities of the PARP enzyme and HSP90 affinity. Our results indicated that compound 4 could bind to HSP90 and cause static quenching, indicating that compound 4 was able to bind to HSP90, moreover, downstream molecular breast cancer 1 (BRAC-1) was reduced. In conclusion, dual target inhibitors of PARP and HSP90 exhibited stronger selective cytotoxicities against cancer.